Development and precision evaluation of a robotic system for oral implant surgery using personalized digital guides and optical spatial positioning technology - Heqiang Tian; Yurui Yin; Xiang Zhang; Jiezhong Tan; Junqiang Liu (PLoS ONE, 2025)
Oral implant surgery demands a high level of precision and expertise, making the integration of robotic assistance an optimal solution. This study introduces an innovative dental implant robotic system designed to enhance accuracy during cavity preparation by combining robotic technology, optical spatial positioning, and personalized digital implant guides. The system employs an EC66 six-degree-of-freedom robotic arm, integrated with digital implant guides and optical navigation technology. A customized implant guide mapping device was developed, fabricated, and validated for its guiding accuracy through meticulous registration and measurement processes. The robotic system’s coordinate systems were thoroughly analyzed, and hand-eye calibration, along with tool calibration, was implemented to ensure synchronized spatial transformations and complete spatial information registration.The robotic system demonstrated superior angular precision in cavity preparation, significantly reducing angular deviation compared to traditional manual methods (4.17 ± 0.28° vs. 5.23 ± 0.10°). However, no significant differences were found in top surface deviation (1.09 ± 0.37 mm vs. 1.43 ± 0.06 mm) or root surface deviation (1.49 ± 0.57 mm vs. 2.57 ± 0.10 mm) between the robotic and manual approaches. These results indicate that while the robotic system excels in angular control, surface deviations in the top and root regions remain comparable to those achieved through manual methods. The system effectively reduces human error, particularly in angular precision, ensuring greater directional control during the procedure. Despite these advancements, further improvements are needed in model and template printing precision, as well as optimization of calibration methods, to minimize residual errors and enhance overall accuracy.This study presents a novel and reproducible approach for assessing the accuracy of implant guides and robotic positioning systems. By showcasing the potential of robotic systems to improve surgical precision and outcomes in dental implantology, this research offers valuable insights for future clinical applications and technological advancements in the field.